2015
DOI: 10.3856/vol43-issue1-fulltext-10
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the temporal and taxonomic patterns of ichthyofauna captured with a fyke net in two sheltered environments in southern Brazil

Abstract: ABSTRACT. We use two taxonomic indexes to assess the variability of the taxonomic structure and diversity of the ichthyofauna of two low-energy environments in southern Brazil and to compare the temporal patterns of these two ichthyofaunas. Sampling was conducted in the infralittoral zones of Maciel (Paranaguá Bay, PR) and Indio Beach (Norte Bay of Florianópolis, SC). A fyke net was set up at a depth of 0.5 to 2.0 m and left in place for 48 h for each of the samplings. A total of two diurnal and two nocturnal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…However, spatial and temporal assemblage patterns were not evaluated. Despite the dominance of a few species, which is a remarkable feature in lagoon and estuarine environments due to significant changes in physical and chemical variables (Day et al, 1989), there are differences in abundance between seasons and areas, commonly present in other surveys conducted in shallow areas (Spach et al, 2010;Contente et al, 2011;Vilar et al, 2011;Souza-Conceição et al, 2013;Cartagena et al, 2014;Ribeiro et al, 2014;Soeth et al, 2015;Cattani et al, 2016a). The use of such environments by juveniles, generally zoobenthivorous, is characterized by the availability of food associated with the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…However, spatial and temporal assemblage patterns were not evaluated. Despite the dominance of a few species, which is a remarkable feature in lagoon and estuarine environments due to significant changes in physical and chemical variables (Day et al, 1989), there are differences in abundance between seasons and areas, commonly present in other surveys conducted in shallow areas (Spach et al, 2010;Contente et al, 2011;Vilar et al, 2011;Souza-Conceição et al, 2013;Cartagena et al, 2014;Ribeiro et al, 2014;Soeth et al, 2015;Cattani et al, 2016a). The use of such environments by juveniles, generally zoobenthivorous, is characterized by the availability of food associated with the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…bays, lagoons and mangroves) of the Island of Santa Catarina (e.g. Clezar et al1997, Nemar 1999, Daura Jorge 2007, Cartagena et al 2011, Soeth 2015, Cattani et al, 2016a, Cattani et al, 2016b, Cattani et al, 2018.…”
Section: Data Collectionmentioning
confidence: 99%
“…Despite the great variety of ecosystems, knowledge about fish assembly from the Island of Santa Catarina is scarce. Only a few studies have been conducted, which focused on spatio-temporal patterns in specific environments (Clezar et al 1997, Ribeiro et al 1997, Ribeiro et al 1999, Cartagena et al 2011, Soeth 2015. Therefore, this study aimed to present a checklist of marine fishes from different coastal environments of the Island of Santa Catarina through a compilation of unpublished and published information from the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In order to minimize the bycatch in shrimp fisheries, many researchers have been suggesting the development of bycatch reduction devices (BRD) as an alternative to fisheries management (Andrew et al 1993, Broadhurst and Kennelly 1996, Broadhurst 2000. The overwhelming majority of published records was devoted to BRDs in shrimp trawls and only few efforts were intended to reduce bycatch in other shrimp fisheries (Larocque et al 2012, Colotelo et al 2013, Soeth et al 2015. It has been widely known that shrimp fyke nets catch an excessive number of different bony fishes that usually are discarded after the fishing activity but only few authors suggested low-cost alternatives to reduce this problem (Vianna andD'Incao 2006, Soeth et al 2015).…”
Section: Introductionmentioning
confidence: 99%